2015
DOI: 10.1371/journal.pone.0127108
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human RSV Immunity at the Molecular Level: Learning from the Past and Present

Abstract: Human RSV is one of the most prevalent viral pathogens of early childhood for which no vaccine is available. Herein we provide an analysis of RSV epitope data to examine its application to vaccine design and development. Our objective was to provide an overview of antigenic coverage, identify critical antibody and T cell determinants, and then analyze the cumulative RSV epitope data from the standpoint of functional responses using a combinational approach to characterize antigenic structure and epitope locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In first-in-human studies, DS-Cav1 elicited neutralizing Abs (NAbs) to the pre-F surface (23). Studies interrogating the structure of the F protein and RSV NAbs identified the most effective epitopes, sites 0 and V, which are exposed only in the pre-F conformation (19,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…In first-in-human studies, DS-Cav1 elicited neutralizing Abs (NAbs) to the pre-F surface (23). Studies interrogating the structure of the F protein and RSV NAbs identified the most effective epitopes, sites 0 and V, which are exposed only in the pre-F conformation (19,24,25).…”
Section: Introductionmentioning
confidence: 99%